(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Oral health plays an important role in overall health of the body because it has a close relation to optimal physical health. Healthy oral cavity does not merely mean caries free teeth, but it means healthy gums and supporting structures. Most prevalent yet preventable disease of oral cavity is dental caries which is a multifactorial disease but is mostly caused by the vertical transmission of S.mutans. Children under the age of 12 are mostly influenced by their surroundings, especially mothers. So, mothers’ literacy rate has a direct influence on their oral health. To improve the overall incidence rate and burden of dental caries in children, it is important that we educate mothers regardless of their socioeconomic status. Aim: The aim of the study was to collect baseline data to evaluate Maternal Education and it’s role shaping children’s oral health. Method: This cross-sectional study was conducted amongst the general population of Lahore. A total of 392 mothers having children from 0-12 years of age were included. A questionnaire containing 23 questions was distributed and the results were recorded. Quantitative variables like age and number of children were presented in the form of mean and standard deviation. Qualitative data like intake of sugary food, frequency of brushing, etc. were presented in the form of frequency and percentages. A chi-square analysis was conducted to examine the association between maternal education level and responses to oral health-related questions Results: In this study, 44.9% of mothers had an education level up to the bachelor’s degree. The results showed significant associations (p < 0.05) between education level and several key aspects of children’s oral health like awareness about caries, excessive sugary food intake (81.1%), the impact of bottle feeding on caries (71.2%), the effect of decayed milk teeth on permanent teeth (50.5%), fluoride’s role in preventing caries (55.4%), and effect of prolonged thumb sucking or bottle feeding (69.4%). However, no significant associations were found regarding the impact of breastfeeding, bacterial transmission, dental infections leading to other problems, or the likelihood of children developing caries if parents have decayed teeth. Conclusion: The study highlights the need for targeted oral health education programs for mothers, as knowledge about oral health is limited. These programs should focus on educating mothers to reduce the oral disease burden.